Programming solutions for economics and business - Nwaobi, Godwin Chukwudum (Abuja, Nigeria Quantitative Economic Research Bureau, 2004)
The book is designed to substantially improve the productivity of modelers and greatly expand the extent and usefulness of mathematical programming applications in policy analysis and decision making.
Includes bibliographical reference and index
opc 17/01/17
Loans
Keywords: Programming- Computers; Economics -- Mathematical models; Business mathematics; Economic theory